Neoadjuvant Chemotherapy with Taxane and Platinum Followed by Radical Hysterectomy for Stage IB2-IIB Cervical Cancer: Impact of Histology Type on Survival - Matsuo, Koji (J Clin Med, 2019)
The current study examined the histology-specific impact of neoadjuvant chemotherapy (NACT) with a taxane/platinum regimen on survival in women with locally-advanced cervical cancer who underwent radical hysterectomy. This nation-wide retrospective cohort study examined women with clinical stage IB2-IIB cervical cancer who received NACT prior to radical hysterectomy from 2004–2008 (n = 684). NACT type (taxane/platinum versus others) was correlated with survival based on histology: 511 squamous versus 173 non-squamous. Taxane/platinum chemotherapy use was more common in non-squamous compared to squamous tumors (53.8% versus 20.7%, P < 0.001). In both histology types, the taxane/platinum regimen was more frequently utilized over time (both, P < 0.01). Among squamous tumors, women who received taxane/platinum chemotherapy had survival comparable to those who received other regimens: 5-year rates for disease-free survival, 69.0% versus 70.1%, P = 0.98; and cause-specific survival, 80.0% versus 81.0%, P = 0.93. Similarly, in non-squamous tumors, disease-free survival (5-year rates: 60.4% versus 59.0%, P = 0.86) and cause-specific survival (74.7% versus 76.3%, P = 0.70) were similar. In conclusion, use of taxane/platinum regimens for NACT significantly increased during the study period. Irrespective of histology type, in women with clinical stage IB2-IIB cervical cancer who underwent NACT prior to radical hysterectomy, taxane/platinum regimens had a similar effect on survival compared to non-taxane/platinum regimens.